Effects of laser pulse modulation on intermetallic compounds formation for welding of Ti-6Al-4V and AA7075 using AA4047 filler. (January 2022) - Liu, Shibo; Chew, Youxiang; Weng, Fei; Sui, Shang; Du, Zhenglin; Man, Yijun; Ng, Fern Lan; Bi, Guijun
Graphical abstract: Highlights: Laser pulse modulation determines the dwell time and affects the intermetallic compounds thickness. Laser pulse modulation influences bubble formation in the melt pool and final porosity. Two intermetallic compounds are formed, TiAl and Al3 Ti. The tensile properties correlate to the change of the IMC thickness. Abstract: Laser welding of titanium and aluminum alloys usually generates pores and brittle intermetallic compounds (IMCs), which degrade the weld mechanical properties. In this study, pulse wave (PW) Nd: YAG laser was used to weld Ti-6Al-4V to aluminum alloy 7075 (AA7075) with aluminum alloy 4047 (AA4047) filler using pulse modulation to control the formation of pores and IMCs. The effect of pulse modulation on porosity levels and IMC layer thickness were analyzed. EBSD, XRD and elemental mapping identified that IMC layers of TiAl and Al3(Ti, V) were formed. A numerical model for pulse laser welding Ti/Al alloys was developed and validated with thermocouple measurements. The numerical results revealed that the predicted cooling rates above the allotropic transformation temperature (882 ℃) of Ti for different pulse modulations have significant correlation with the measured IMC layer thickness. The optimized process parameters with pulse modulation were able to control the IMC thickness to within 5 µm and attain a maximum ultimate tensile strength of 158 MPa.